Cyclohexene oxide CA, a derivative of zeylenone, exhibits anti-cancer activity in glioblastoma by inducing G0/G1 phase arrest through interference with EZH2 - Su, Rui; Cao, Weiwei; Ma, Guoxu; Li, Weiping; Li, Zongyang; Liu, Yongpei; Chen, Lei; Chen, Zebin; Li, Xuejuan; Cui, Ping; Huang, Guodong (Frontiers in Pharmacology, 2024)
Due to its highly aggressiveness and malignancy, glioblastoma (GBM) urgently requires a safe and effective treatment strategy. Zeylenone, a natural polyoxygenated cyclohexenes compound isolated from Uvaria grandiflora, has exhibited potential biological activities in various human diseases, including tumors. In this study, we designed and synthesized a series of (+)-Zeylenone analogues and evaluated their anti-GBM roles through structural-activity analysis. We identified CA ((1R, 2R, 3S)-3-p-fluorobenzoyl-zeylenone) as having the lowest IC50 value in GBM cells. CA treatment significantly inhibited the malignant behaviors of GBM cells and induced G0/G1 phase arrest in vitro. Furthermore, we validated the molecular mechanism by which CA interferes with EZH2, attenuating the down-regulation of cyclin-dependent kinase inhibitors p27 and p16 by the PRC2 complex. By establishing orthotopic nude mice models, we further validated the inhibitory role of CA on tumorigenesis of GBM cells in vivo and its potential values to synergistically potentiate the anti-tumor effects of EZH2 inhibitors. Overall, this paper elucidated the anti-GBM effects and potential mechanisms of CA, and may provide a therapeutic drug candidate for GBM treatment.